From respect to revelation: bridging hearts through da’wah in Japan - a practical guide to effective da’wah in Japanese society - Abdul Latif @ Bapoo, Lilisuriani; Johari, Arina; Yusof, Syahirah (KSTCL Press, IIUM, 2025)
This research-based guide provides a practical approach for those who wish to share the message of Islam within the unique cultural setting of Japan. It begins by outlining the general characteristics of the Japanese people and the main challenges involved in performing da’wah, before moving on to suggestions for how one can prepare oneself for this task. Practical ways of engaging with the Japanese community are then explored, with examples of effective communication and common pitfalls to avoid. Ultimately, the guide is not just about techniques, but about transforming da’wah into a compassionate and respectful invitation — one that builds bridges of understanding and leaves a lasting impression of Islam’s beauty.